2022
DOI: 10.3390/f13010055
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Variation of Wild Sweet Chestnut (Castanea sativa Mill.) Populations

Abstract: Sweet chestnut (Castanea sativa Mill., Fagaceae) is one of the oldest cultivated tree species in the Mediterranean, providing multiple benefits, and, since it has edible seeds, it represents an interesting model species for the research of morphological and chemical variability. In this study, morphometric methods and chemical analyses were used to quantify the extent of differences in phenotypic and nutritional traits between eight natural populations of sweet chestnut from different environmental conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…A similar pattern of total variance distribution was reported by other authors (Poljak et al, 2022;Xu et al, 2016) when fruit/cone morphological variability of woody taxa is concerned. However, this rule of variability distribution was not observed for variables FL/FW and ST/SW.…”
Section: Discussionsupporting
confidence: 88%
“…A similar pattern of total variance distribution was reported by other authors (Poljak et al, 2022;Xu et al, 2016) when fruit/cone morphological variability of woody taxa is concerned. However, this rule of variability distribution was not observed for variables FL/FW and ST/SW.…”
Section: Discussionsupporting
confidence: 88%
“…The results did not reveal the existence of a significant correlations between phytochemicals/MTs and climate/geographical data. Similar studies [ 76 ] have shown that chemical and morphological variability are not always associated with geographical and environmental variables. For a better characterization of interpopulation correlations, similar studies of (IBD) and (IBE) were performed using bioclimatic variables and genetic distances [ 77 ].…”
Section: Discussionsupporting
confidence: 68%
“…Similar patterns of variability in leaf and fruit traits were found in other species as well: Castanea sativa Mill. [74][75][76][77], Ulmus laevis Pall [78] and Sorbus domestica L. [79].…”
Section: Discussionmentioning
confidence: 99%